The Impact of Urban Culture on Street Vending: A Path Model Analysis of the General Public's Perspective - Al-Jundi, Salem A.; Al-Janabi, Haitham A.; Salam, Mohammad Asif; Bajaba, Saleh; Ullah, Shakir (Frontiers in Psychology, 2022)
This study examined the relationship between urban culture and street vending. Prior research on this topic is limited and inconclusive. Therefore, we have proposed an integrated model to test the positive effect of urban culture on street vending using multiple mediations of consumption patterns, resistance, and microfinance. We tested a sample of 425 responses that reflect the public opinion in Baghdad, Iraq. These responses were collected between September and November 2018. A partial least squares–based structural equation modeling is employed to test the validity of measurement models and the significance of the entire structural model, predictive power, and mediation analysis. We found that resistance mediates the effect of urban culture on street vending; low-income consumption and resistance sequentially mediate the effect of urban culture on street vending, while resistance mediates the effect of a lack of microfinance on street vending. The direct impact of culture on street vending is not significant, and a lack of microfinance positively influences the pervasiveness of trading on streets. This study contributes to the extant literature as it proposed and tested a novel and comprehensive model to analyze the relationship between urban culture and street vending, simultaneously examining the effects of culture, consumption, resistance, and microfinance on street vending.